Case Report: Self-Administration of Omalizumab in an Adolescent With Severe Asthma During SARS-CoV-2 Infection - Paladini, Erika; Giovannini, Mattia; Barni, Simona; Liccioli, Giulia; Sarti, Lucrezia; Novembre, Elio; Mori, Francesca (Frontiers in Pediatrics, 2021)
Acute asthma remains one of the most frequent causes of children's access to healthcare. Asthma exacerbation is an essential defining characteristic of its severity, and respiratory infections entail increased risks of exacerbations with potential hospitalization. In literature, contradictory findings have been reported about the risk and severity of Severe Acute Respiratory Syndrome Coronavirus 2 infection in patients affected by asthma, with several implications for the management of the latter. Anti-IgE monoclonal antibodies therapy is meant for patients affected by severe asthma without adequate control with other treatments. Indeed, biological therapies, like omalizumab, are used as add-on treatments (step 5 in the Global Initiative for Asthma report ) for severe asthma with several benefits, including the reduction in the frequency of exacerbations. To the best of our knowledge, we hereby report the first case in which an adolescent with severe allergic asthma treated with omalizumab has switched to self-administration at home during SARS-CoV-2 infection. In the light of our peculiar experience, physicians may consider switching to self-administration of omalizumab at home, even during the Coronavirus Disease 2019 pandemic. However, more extensive research data from future studies are needed to confirm these first findings.